A highly sensitive homogeneous electrochemical assay for alkaline phosphatase activity based on single molecular beacon-initiated T7 exonuclease-mediated signal amplification. Issue 12 (21st June 2015) - Zhang, Lianfang; Hou, Ting; Li, Haiyin; Li, Feng
<x xml:space="preserve">Abstract</x> A highly sensitive homogeneous electrochemical assay for alkaline phosphatase activity based on single molecular beacon-initiated T7 exonuclease-assisted signal amplification.